In-vivo toxicity of Prophet's medicinal plant, lawsonia inermis (henna) leaves - Talik Sisin, Noor Nabilah; Darnis, Deny Susanti (2014)
Lawsonia inermis (henna) is always being explored solely for its scientific components, not for its usage as the Prophetic medicine. Although henna is a popular medicinal plant around the world, only scant toxicity studies have been reported about Malaysia henna and hardly any study that investigated histopathological changes of liver and kidneys of mice due to administration of henna leaves extracts. Antiurolithiatic effect of Malaysian henna in-vitro had been proven and in order to continue study the effect in-vivo, toxicity of the henna towards kidneys should be determined first. The objectives of this study are to observe acute oral toxicity effect of the hydroethanolic (75 % ethanol) extract of henna leaves on behavioural and clinical patterns of the mice and to compare the histopathological changes between control and treatment groups of the mice. Leaves were extracted using soxhlet with hydroethanolic solvent. Single oral dose of 2000 mg/kg henna leaves extracts diluted with distilled water were assigned to treatment group of mice while control group was given distilled water only. Observations were done for 14 days and the mice were sacrificed. Selected organs were taken and weighed but only livers and kidneys were taken for histological assessments. Overall, the behavioral and clinical patterns of the mice were observed to be normal. Biostatistically, all selected organs’ means weight between control and treatment groups are not statistically significant (p>0.05). Furthermore, the irregularities found were not very apparent when histopathological examinations were done. Even though there was not death occurred during the experimental period and no gross changes were observed, there were degeneration of connective tissues between the tubules of the kidneys and pyknotic nuclei within hepatocytes. In conclusion, it is scientifically proven that single dose of hydroethanolic extract of L. inermis (henna) leaves can cause toxicity towards liver and kidneys of the mice.